2016
DOI: 10.3389/fphar.2016.00097
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antihypertensive and Antihyperlipidemic Effects of the Crude Extracts and Fractions of Moringa stenopetala (Baker f.) Cufod. Leaves in Rats

Abstract: Background: Moringa stenopetala (Baker f.) Cufod. is a medicinal plant that has been used in Ethiopian traditional medicine as a remedy for treatment of hypertension and diabetes. The aim of this study was to evaluate antihypertensive and antihyperlipidemic effect in fructose induced hypertensive rats.Methods: Rats were randomly divided into control and treatment groups (n = 6). Treatment groups were given daily extracts (250, 500, and 1000 mg/kg) orally with fructose. Whereas, positive, negative and normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 22 publications
1
44
1
Order By: Relevance
“…Several scientific studies have also confirmed that the various parts of the plant possess anti-malarial, antileishmenial and anti-fertility [50], hypotensive [40], anti-hypertensive [7], vasodilatory [51], hypoglycemic [52], and anti-diabetic effects [47,53].…”
Section: The Role Of Herbal Medicines In Management Of Hypertensionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several scientific studies have also confirmed that the various parts of the plant possess anti-malarial, antileishmenial and anti-fertility [50], hypotensive [40], anti-hypertensive [7], vasodilatory [51], hypoglycemic [52], and anti-diabetic effects [47,53].…”
Section: The Role Of Herbal Medicines In Management Of Hypertensionmentioning
confidence: 99%
“…The hydroethanol extract of the plant has shown a significant urine output at all doses and significantly increased the excretion of Na + and Cl -at higher doses [54]. These pharmacological activities might be attributed to presence of different phytochemical constituents found in the plant extract, especially glycosides and alkaloids [7,51]. Safety and toxicity: Ghebreselassie et al evaluated the effects of aqueous leaf extract of Moringa stenopetala on blood parameters, and the histopathology of liver and kidney in experimental mice [55].…”
Section: The Role Of Herbal Medicines In Management Of Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations